Racial disparities in out-of-hospital cardiac arrest interventions and survival in the Pragmatic Airway Resuscitation Trial. (October 2020) - Lupton, Joshua R.; Schmicker, Robert H.; Aufderheide, Tom P.; Blewer, Audrey; Callaway, Clifton; Carlson, Jestin N.; Colella, M. Riccardo; Hansen, Matt; Herren, Heather; Nichol, Graham; Wang, Henry; Daya, Mohamud R.
Abstract: Background: Prior studies have reported racial disparities in survival from out-of-hospital cardiac arrest (OHCA). However, these studies did not evaluate the association of race with OHCA course of care and outcomes. The purpose of this study was to evaluate racial disparities in OHCA airway placement success and patient outcomes in the multicenter Pragmatic Airway Resuscitation Trial (PART). Method: We conducted a secondary analysis of adult OHCA patients enrolled in PART. The parent trial randomized subjects to initial advanced airway management with laryngeal tube or endotracheal intubation. For this analysis, the primary independent variable was patient race categorized by emergency medical services (EMS) as white, black, Hispanic, other, and unknown. We used general estimating equations to examine the association of race with airway attempt success, 72-h survival, and survival to hospital discharge, adjusting for sex, age, witness status, bystander cardiopulmonary resuscitation (CPR), initial rhythm, arrest location, and PART randomization cluster. Results: Of 3002 patients, EMS-assessed race as 1537 white, 860 black, 163 Hispanic, 90 other, and 352 unknown. Initial shockable rhythms (13.8% vs. 21.5%, p < 0.001), bystander CPR (35.6% vs. 51.4%, p < 0.001), and survival to hospital discharge (7.6% vs. 10.8%, p = 0.011) were lower for black compared to white patients. After adjustment for confounders, no difference was seen in airway success, 72-h survival, and survival to hospital discharge by race. Conclusions: In one of the largest studies evaluating differences in prehospital airway interventions and outcomes by EMS-assessed race for OHCA patients, we found no significant adjusted differences between airway success or survival outcomes.